Humor and politics in the deconstruction of superheroes in Latin America during the Cold War: the look of comics (Revista Tempo e Argumento, 2016)
A medium associated with everyday life and juvenile entertainment, comics achieved full consolidation in Latin America in the post-Second World War years. During the Cold War and the massive U.S. cultural penetration in the region, comics were already seen in newspapers, where they were sometimes published in specific supplements, and also edited as comic books by specialized publishing houses. Amid debates about the advantages and disadvantages of comics for life that already mobilized those involved in the world of comics, the issue of cultural imperialism also led critics and local production to seek redefining the meanings of this medium in Latin America. One of the steps involved the effective defense of a “substitution of imports” from foreign producers, with a focus on the local creation of comics that could represent the national reality. To do this, there was a need to deconstruct some references from foreign comics, in order to put them into question before their reading community. This article analyzes this process through two case studies: the Brazilian cooperative CETPA (Cooperativa Editora de Trabalhos de Porto Alegre) and the Chilean publishing house Quimantú. In both of them, the focus primarily lied on superheroes, mixing parody and political criticism when discussing the superhero’s action in Latin America. Through the situations under analysis, we highlight this step for establishing comics as a cultural practice in the region. Keywords: Comics; Superheroes; Latin America – History